Aprendizagem sobre queda livre dos corpos por meio de uma sequência de ensino investigativa - SEI - Reis, Thaís Alves (2024)
The formation of critical and active citizens in the face of technological and scientific advances in modern society is desired by many researchers in the field of education. For such training, it is necessary to teach science that develops our students, in addition to learning concepts, also procedures and attitudes. In this context, teaching through investigation through Investigative Teaching Sequences (SEIs) is understood by many authors as promising, as it is a teaching and learning process that promotes in student’s characteristicsthat enhance the development of scientific attitudes and the understanding of skills natural. . Therefore, it makes students active in building their own knowledge, to promote the ability to argue, communicate and create strategiesthat enable the elucidation of problems. Therefore, thisresearch aimed to analyze the learning developed by students during the experience of an SEI on the Free Fall content, in order to identify and characterize evidence of learning in terms of concepts, attitudes and procedures developed by students during the experience of an SEI that was based on the investigative activities described by Carvalho (2013). This work is based on the constructivist ideals of Piaget and Vygotsky for education and studies regarding learning content (concepts, procedures, and attitudes). The research approach was qualitative and was also an interventional research based on the type of application. For data collection, two questionnaires were considered, one pre-test and the other post-test, prepared by the researcher and answered by students from a 1st year high school class at the Federal Institute of Sergipe, Campus Lagarto; records of activities carried out at SEI and audio recorded during the SEI experience were also analyzed. Data analysis was carried out using the stages of Bardin's Conditional Content Analysis technique (2011). The results obtained show that the investigative activitiesdeveloped at SEI were designed to develop concepts, procedures, and attitudes by students. Thus, SEI's proposal to approach Free Fall presents itself as a didactic strategy with great potential for the science teaching and learning process, which can contribute to the formation of critical and active citizens.